SYMMETRIC AND ASYMMETRIC PHOTOFISSION MODES $^{232}$Th AT INTERMEDIATE ENERGIES - Demekhina, N. A.; Karapetyan, G. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2007)
The 232Th photofission yields were measured by using bremsstrahlung at end-point energy of 50 and 3500 MeV. The nuclear charge and mass distributions of the fission fragments were obtained. The multi-modal fission approach was used for calculation of the symmetric and asymmetric channels in the photofission. The behaviour of asymmetric-symmetric components and 232Th fissility by different channels were obtained at the intermediate energies.
Keywords: bremsstrahlung at end-point energy; photofission; fissility by different channels